Formulation of melamine urea formaldehyde (MUF) resin by using various types of filler - Norliza, Ishak (2012)
The performance of adhesive in term of working properties and quality is improved by the types of material use as filler. Industrial Flour (IF), Pre treatment and post treatment Palm Kernel Meal (PKM) and Palm Kernel Cake (PKC) are chosen for this research as filler for the comparison in wood adhesive production. Melamine Urea Formaldehyde (MUF) resin is selected as the resin for wood adhesive production because of less costly and high water resistant compared to Melamine Formaldehyde (MF) and Urea Formaldehyde (UF) resins (Dunky, 2003). This is because the cost of MUF resins depends on the ratio of melamine and urea. The objective is to compare the types of filler use for wood adhesive production in term of working properties and its quality. The shear strength and wood failure for wood adhesive was studied to determine the working properties of plywood. The experiments were conducted with temperature in specific range and the pressing time from 50s to 350s. The sieve shaker experiment will be done by using different type of sieve to get the different sizes of filer’s particle size, to use the uniform size of fillers. The research study can be conclude that the better performance of wood adhesive in term of mechanical properties likes strength, durability and quality are based on materials which is types of filler use whether using Industrial Flour (IF), pre treatment and post treatment Palm Kernel Meal (PKM) or Palm Kernel Cake (PKC). The optimum value of temperature and pressing time were determined using Response Surface Methodology (RSM).